The influence of players` nationality on the effectiveness of eSports teams based on the example of The International DOTA 2 tournaments - Kołodziej, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented text addresses the issue of the influence of national diversity of eSports teams on their effectiveness in winning DOTA 2 games. The analyses were based on data concerning the entire population of teams participating in The International series tournaments. The results of the analyses confirm the hypothesis that teams with a strong national diversity, more often than teams with a high national homogeneity, achieve a high effectiveness coefficient and occupy a high place in the final classification of the analyzed tournaments.
Keywords: national diversity; eSport; eSports teams effectiveness; DOTA 2; eSports team diversity